2021
DOI: 10.1017/gmh.2021.36
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and opportunities for refugee mental health services: clinician recommendations from Jordan

Abstract: Background Jordan has received more than three million refugees from bordering countries during times of conflict, including over 600 000 Syrian refugees between 2011 and 2021. Amidst this humanitarian crisis, a new mental health system for Syrian refugees has developed in Jordan, with most clinical services administered through non-governmental organizations. Prior studies have identified increased risk of psychiatric disorders in refugee populations and significant barriers for Syrian refugees seeking m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Also, previous studies documented increased risk of mental health problems among camp refugees and significant barriers for Syrian refugees seeking mental health treatment; this demonstrated that the Syrian camp refugee in Jordan continues to face significant stressors including symptoms of distress and reduced functioning in people’s daily activities due to their experience of emotional distress [ 9 ]. Shortage of mental health professionals, medication shortages, poor awareness of available mental health services, limited or absent screening protocols, and the financial hardship of refugee patients are significant limiting factors to accessing mental healthcare [ 29 ]. Therefore, the integration of the UNODC’s parenting skills material is timely and useful [ 13 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, previous studies documented increased risk of mental health problems among camp refugees and significant barriers for Syrian refugees seeking mental health treatment; this demonstrated that the Syrian camp refugee in Jordan continues to face significant stressors including symptoms of distress and reduced functioning in people’s daily activities due to their experience of emotional distress [ 9 ]. Shortage of mental health professionals, medication shortages, poor awareness of available mental health services, limited or absent screening protocols, and the financial hardship of refugee patients are significant limiting factors to accessing mental healthcare [ 29 ]. Therefore, the integration of the UNODC’s parenting skills material is timely and useful [ 13 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies revealed trust as an important barrier. Immigrant and refugee populations in two studies expressed distrust in western mental health care systems (62, 94), and this was supported by one study with mental health professionals working with refugees (51). Issues surrounding mistrust and lack of con dence in competency and transparency of professionals were revealed, mostly in refugee and immigrant samples.…”
Section: Cultural Barriersmentioning
confidence: 89%
“…Language and communication barriers were reported in ten studies, primarily by refugee populations and Arabs in non-Arabic speaking countries. Service providers working with a refugee population in one study mutually reported language as a barrier (51). Individuals reported di culties in approaching professionals due to language barriers nding it challenging to express themselves.…”
Section: Languagementioning
confidence: 99%
“… 37 However, refugee camps continue to face the issue of a severe shortage of healthcare workers ( Figure 3 ). 12 A 2016 study conducted by the Johns Hopkins Bloomberg School of Public Health estimated that 59.5 million displaced individuals globally required 2.78 million surgical procedures. 20 However, a sizable portion of these urgent surgical needs have not been met as a result of several issues, including a surgeon shortage.…”
Section: Challenges In Managing Surgical Diseases In Global Refugee P...mentioning
confidence: 99%
“…This approach involves increasing funding for healthcare programmes, improving training and retention of healthcare workers and fostering coordination between humanitarian organisations and local healthcare systems. 11 , 12 By addressing these challenges, it becomes possible to alleviate the burden of surgical diseases and improve the overall health outcomes of the global refugee population. Thus, this review aims to explore the impact of various factors on the burden of surgical diseases among refugees and identify potential strategies for improvement.…”
Section: Introductionmentioning
confidence: 99%